Application of Information Technology in Increasing Effectiveness, Efficiency and Production of Halal Culinary MSMEs in Dompu Regency - Munawarah, Hazratul; Irwansyah, Irwansyah; Ramadhan, Rizky (Business Management, 2025)
This research aims to determine the application of information technology in increasing the effectiveness, efficiency and halal culinary production of MSMEs in Dompu Regency. The research method used in this research is qualitative research, with a descriptive approach. In general, qualitative data collection techniques in this research that are often used by social researchers include; observations, interviews and literature studies or library studies (documentation) to Sina Cake Dompu. With information consisting of owners, managers and staff, the research results explain that the application of information technology to halal culinary MSMEs such as Sina Cake Dompu has had a positive impact in increasing effectiveness, efficiency and production. By utilizing digital technology, operational processes become more organized and opportunities for market expansion open up. Therefore, MSMEs need to continue to adopt technological innovation in order to survive and develop.